Highly sensitive and specific bioassay for measuring bioactive TGF-β - Tesseur, Ina (BioMed Central, 2006)
BACKGROUND: Transforming Growth Factor-β (TGF-β) regulates key biological processes during development and in adult tissues and has been implicated in many diseases. To study the biological functions of TGF-β, sensitive, specific, and convenient bioassays are necessary. Here we describe a new cell-based bioassay that fulfills these requirements. RESULTS: Embryonic fibroblasts from Tgfb1(-/- )mice were stably transfected with a reporter plasmid consisting of TGF-β responsive Smad-binding elements coupled to a secreted alkaline phosphatase reporter gene (SBE-SEAP). Clone MFB-F11 showed more than 1000-fold induction after stimulation with 1 ng/ml TGF-β1, and detected as little as 1 pg/ml TGF-β1. MFB-F11 cells were highly induced by TGF-β1, TGF-β2 and TGF-β3, but did not show induction with related family members activin, nodal, BMP-2 and BMP-6 or with trophic factors bFGF and BDNF. MFB-F11 cells can detect and quantify TGF-β in biological samples without prior enrichment of TGF-βs, and can detect biologically activated TGF-β in a cell co-culture system. CONCLUSION: MFB-F11 cells can be used to rapidly and specifically measure TGF-β with high sensitivity.